One-Dimensional Consolidation of Double-Layered Foundation with Depth-Dependent Initial Excess Pore Pressure and Additional Stress - Junhui Zhang; Guangming Cen; Weizheng Liu; Houxuan Wu (Advances in Materials Science and Engineering)
A model for one-dimensional consolidation of a double-layered foundation considering the depth-dependent initial excess pore pressure and additional stress and time-dependent loading under different drainage conditions was presented in this study and its general analytical solution was deduced. The consolidation solutions of several special cases of single-drained and double-drained conditions under an instantaneous loading and a single-level uniform loading were derived. Then, the average degree of consolidation of the double-layered foundation defined by settlement was gained and verified. Finally, the effects of the initial excess pore pressure distributions, depth-dependent additional stress, and loading modes on the consolidation of the soft foundation with an upper crust with different drainage conditions were revealed. The results show that the distributions of initial excess pore pressure and additional stress with depth and loading rates have a significant influence on the consolidation process of the soft foundation with an upper crust. This influence is larger with the single-drained condition than that with the double-drained condition. Comparing the consolidation rate with a uniform initial pore pressure and additional stress, their decreasing distribution with depth quickens the consolidation at the former and middle stages. Moreover, the larger the loading rate is, the quicker the consolidation of the soft foundation with an upper crust is.